2017
DOI: 10.1515/bmt-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of novel ultrasound-activated bioresorbable pins for the treatment of osteochondral fractures compared to established methods

Abstract: Background:Osteochondral injuries often lead to osteoarthritis of the affected joint. All established systems for refixation of osteochondral defects show certain disadvantages. To address the problem of reduced stability in resorbable implants, ultrasound-activated pins were developed. By ultrasound-activated melting of the tip of these implants, a more secure anchoring is assumed.Materials and methods:The aim of the study was to investigate if ultrasound-activated pins can provide secure fixation of osteocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Alternative resorbable pins have been developed to overcome the necessity for pin removal and have been introduced onto the market [19,[21][22][23]. For example, biodegradable polymer pins based on polyglycolic acid (PGA), polylactic acid (PLA) and other homopolymers and copolymers have been studied to replace titanium devices [24,25]. Additionally, pins obtained from decellularized human or bovine cortical bone have been described [19].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative resorbable pins have been developed to overcome the necessity for pin removal and have been introduced onto the market [19,[21][22][23]. For example, biodegradable polymer pins based on polyglycolic acid (PGA), polylactic acid (PLA) and other homopolymers and copolymers have been studied to replace titanium devices [24,25]. Additionally, pins obtained from decellularized human or bovine cortical bone have been described [19].…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasound fusion process was proven to be highly reproducible. Kienast et al 9 demonstrated that ultrasound-activated PLDLLA pins have comparable anchoring strength to screw fixation in a model of medial femoral condyle osteochondral fragment fixation in sheep.…”
Section: Discussionmentioning
confidence: 99%